2023
DOI: 10.1097/ms9.0000000000000437
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative mortality and its predictors among patients undergoing emergency laparotomy at selected southern Ethiopian governmental hospitals, 2022: a multicenter prospective cohort study

Abstract: Background: Globally, emergency laparotomy is a frequently performed type of surgery with high morbidity and mortality rates, even in the best healthcare systems. There is limited knowledge regarding the outcome of emergency laparotomy performed in Ethiopia. Objective: To assess perioperative mortality and its predictors among patients undergoing emergency laparotomy at selected southern Ethiopian governmental hospitals. Methods: A multicenter pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(32 reference statements)
3
1
0
Order By: Relevance
“…This study revealed that patients who were hypotensive at presentation were 3.87 times more likely to develop perioperative adverse outcomes. These results are consistent with those of previous studies conducted in Ethiopia, Tanzania, and the U.S. 7 , 10 , 32 , 33 Optimization of blood pressure during the perioperative period has been shown to enhance surgical outcomes. According to a systematic review, hypotension increases the likelihood of adverse post-operative outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study revealed that patients who were hypotensive at presentation were 3.87 times more likely to develop perioperative adverse outcomes. These results are consistent with those of previous studies conducted in Ethiopia, Tanzania, and the U.S. 7 , 10 , 32 , 33 Optimization of blood pressure during the perioperative period has been shown to enhance surgical outcomes. According to a systematic review, hypotension increases the likelihood of adverse post-operative outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…This study found that patients with a higher ASA status (ASA II–IV) were 2.37 times more likely to develop perioperative adverse outcomes [AOR: 2.37 (95% CI: (1.05, 5.34))]. This finding was consistent with those of a multicenter study conducted in southern Ethiopia, 32 Cologne (Germany), 45 and Wales (United Kingdom), 46 which demonstrated that the risk of developing post-operative complications was highly influenced by a higher ASA category. This may be attributed to the patients’ poor physical condition and debilitating comorbidities during the pre-operative period.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the admissions in this study, (41 of 45), were with ASA status IE & IIE which contrasts with nationwide databasis in Japan [ 45 ]. Similar studies from Ethiopia and others [ 38 , 46 , 47 ] reported admission to intensive care units to be associated with higher mortality. However, in these studies, 23.8% of patients were admitted at any time to the ICU postoperatively and the 30-day mortality seen among ICU patients was 37.9% which is proportionally higher than found in this study (11.65 and 36.6% respectively).…”
Section: Discussionsupporting
confidence: 80%
“…Patients with severe abdominal sepsis often require an emergency laparotomy, which is associated with higher mortality and morbidity compared to less invasive procedures (Fig. 2 ) [ 12 , 59 , 69 , 90 , 136 , 154 , 162 ]. Possible reasons for poorer outcomes include the trauma of surgery itself amplifying immune cell activation, increasing inflammation, coagulopathy and MODS [ 39 , 41 ].…”
Section: Pathophysiology From a System’s Perspectivementioning
confidence: 99%